The Language Commons: An Innovative Space Supporting Second Language Acquisition - Judith Giering; Hope Fitzgerald (Journal of Teaching and Learning with Technology, 2019)
In 2015, language faculty and administrators at a large public university met to evaluate the needs of the more than 20 language programs offered on campus. A priority emerged for language learning space better equipped to facilitate authentic interaction and communication. The committee conceived of an alternative language learning space that would be motivating, collaborative, and inviting, and offer a variety of technologies in support of innovative teaching and learning.  Now in its second year of operation, the Language Commons facilitates formal and informal learning activities for students and faculty that are aligned with current theory and practice of Second Language Acquisition. Language faculty utilize the space for innovative instructional activities that might otherwise be limited by small, inflexible classroom spaces. This article describes the development of the Language Commons from initial conception through design, and the rich array of activities occurring in the space, featuring examples of faculty uses of Commons spaces and technologies. Preliminary outcomes suggest the Commons is valued for its support of student motivation, lowering of anxiety, opportunities for community engagement, and as a place to disrupt classroom hierarchies and routines.